Abrigos subterrâneos e vestígios da história antiga em Novo Barreiro/RS - Kolling, Lieli Coelho (2020)
Archaeological and paleontological research has considered the incidence of remains from Ancient History and paleoburrows in the South and Southeast regions of Brazil. Inland, the occurrence of these phenomena as well as remnants of occupation still requires more systematic research. It is in this sense that the efforts of this work are inserted. It is equally relevant, as it proposes to enable the Barreirense community to gain knowledge of the municipality's archaeological, historical, cultural and environmental heritage, thus contributing to the appreciation of the space, preservation and understanding of the processes of territorial occupation and historical phenomena that occurred there. Furthermore, it seeks to add the indigenous element to the municipality’s narratives of history and identity. The research sources used were lithic artifacts and paleoburrows. The artifacts are part of the personal collections of residents of the municipality. Visits were carried out to the locations of the finds, analysis and measurement of the remains, as well as plotting, surface prospecting and on-site visits to the paleoburrows. From the analytical and interpretative treatment of the sources, it is possible to attribute the beginning of settlement in the municipality of Novo Barreiro to groups of hunter-gatherers who settled in this region, approximately, at the beginning of the Holocene period, but considering that previously the territory was occupied by giant mammals during the megafauna period.